Nitrogen Management for Teff Hay Production - D. H. Min; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2015)
Fertilization of teff with nitrogen (N) resulted in increased forage production, but amounts above 25 lb/a did not often increase yields in this study. Urea as the N source produced at least as much yield response as the alternate, an extended source of nitrogen (ESN).
Keywords: extended-release nitrogen; nitrogen rate; multiple harvests